PROBLEMS OF DOCTOR-PATIENT COMMUNICATION IN MEDICAL PRACTICE. WAYS TO APPROACH THE PATIENT IN COMPLICATED CASES - Ana Maria Alexandra Stănescu; Ioana Veronica Grajdeanu; Ovidiu Gabriel Bratu; Cristina Olariu; Mihaela Adela Iancu; Ioana Florentina Codreanu; Camelia Cristina Diaconu (Romanian Medical Journal, 2018)
Currently, the physician-patient relationship is a bidirectional one, the center of which is communication. Communication is no longer regarded as an option but as a necessity in the day-to-day practice of physicians. The way we use communication can make a big difference on the physician-patient relationship, on the understanding of the disease, the treatment, and on the subsequent conduct of the patient. The approach to this subject comes in the absence of formal courses for doctors in communication, a necessary and beneficial thing both for the doctor and for the patient.